Switching Barrier Effect on Millennial Customer Retention through the Mediation of Brand Trust - Agung Novianto Margarena; Nurhidayani Nurhidayani; Amanda Yuliana; Agung Budiarto (Almana : Jurnal Manajemen dan Bisnis, 2021)
The existence of a business phenomenon between companies in the modern herbal medicine industry related to the difference between switching barriers, brand trust, and customer retention. The purpose of this research was to examine the difference in the relationship between variables to this phenomenon. This study used a purposive sampling method with a total sample of 130 millennials in Surakarta who consumed herbal sachets at least in the last 3 months. The research method used in this study is a quantitative method using SEM analysis tools AMOS version 21.0. This study indicates that the switching barrier affects customer retention significantly both directly and when mediated by brand trust. So in the Modern Herbal Medicine Industry, the development of customer retention is very dependent on switching barriers and brand trust.